(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to evaluate changes in neuropsychiatric indicators and daytime functioning ability when applying a combined acupuncture and massage therapy protocol. Subjects and methods: This clinical intervention study involved 60 patients with insomnia of the Heart-Spleen deficiency type. The study group performed acupuncture combined with massage therapy; the control group only used massage therapy. The main evaluation indicators included: fatigue status, concentration ability, daytime functional disorders, and related psychological trauma. Results: After 15 days of treatment, the fatigue rate in the study group decreased from 100% to 20% (p < 0.05), demonstrating the positive effect of the protocol in improving the patients’ physical condition. Daytime functional disorders (according to PSQI) improved significantly, with 66.7% of patients in the study group no longer experiencing disorders compared to 56.7% in the control group (p < 0.05). Anxiety, irritability, and memory impairment were also significantly reduced in the study group (p < 0.05). Conclusion: The combined protocol comprehensively improved neuropsychiatric status and restored daytime functioning for patients.